Standard Operation Procedure for The Laundry Industry by Considering Thaharah from Uncleanness - Muti, Asri Amalia; Yuniawati, Ratna Diah; Mustaqim, Mustaqim (Jurnal IPTEK, 2024)
In general, the clothing sorting stage is to only separate clothes based on type, color, material and function. Unclean and hadas are not included in the sorting priority. Guaranteeing the quality of products or services is also very clearly stated in article 7 point d of Law no. 8 of 1999 concerning the obligations of business actors to guarantee the quality of goods and/or services produced. In order to prevent fraud by laundry business actors who do not comply with the quality, level, composition, especially the processing process, style or mode as stated on the label or description of goods and/or services, it is necessary to formulate SOPs as a guideline for running a business. The aim of this research is the need for industrial laundry SOPs that consider thaharah, in order to provide confidence and guarantee the quality of service results and raise awareness of consumer protection so that honesty and responsibility can grow. This research has a qualitative approach and validates the SOP document. From the preparation of the SOP, it was recorded that there were 30 activities with a total time of approximately 23,400 seconds or 6.5 hours, the time required was longer than before. Apart from that, there are changes in the sorting process, namely the unclean classification in the first inspection and the color classification in the second classification. The validation result is that the SOP that has been created is in accordance with the thaharah principle. Furthermore, this research can measure work productivity with the aim of increasing efficiency and effectiveness in work processes and time.